The business of streaming and digital media - Rayburn, Dan (Focal Press, 2005)
This book answers the question, "What is the value of using streaming and digital media for my business and what can I expect in return?" The Business of Steaming and Digital Media gives you a concise and direct analysis of how to implement a scalable, profitable venture, as well as the common and hidden pitfalls to avoid in your business. By focusing on both the business implications and technical differences between rich media and traditional broadcast distribution, you will learn how to gain significant time-to-market and cost-saving advantages by effectively using streaming and digital med